Roquin recognizes a non-canonical hexaloop structure in the 3′-UTR of Ox40 - Robert Janowski (Nature Portfolio, 2016)
Roquin is an RNA-binding protein that prevents autoimmunity by limiting expression of receptors such as Ox40. Here, the authors identify an RNA structure that they describe as an alternative decay element, and they characterise its interaction with Roquin using structural and biochemical techniques.